Delay in reaching health facilities and its associated factors among mothers giving birth in South Gondar zone hospitals, Northwest Ethiopia, 2020: A facility-based cross-sectional study - Kassa, Bekalu Getnet; Tiruneh, Gebrehiwot Ayalew; Solomon, Abayneh Aklilu (Frontiers in Global Women's Health, 2023)
Background: Delays in reaching health facilities are one of three models identified as major contributors to maternal mortality and morbidity in developing countries, including Ethiopia. However, little is known about the prevalence and associated factors of delay in reaching health care facilities in Ethiopia, particularly in rural areas. Objective: The aim of this study was to assess the prevalence of delays in reaching health facilities and associated factors among mothers who gave birth in south Gondar zone hospitals, northwest, Ethiopia, 2020. Methods: A cross-sectional study design was used from November 28 to December 25, 2020, with 417 mothers who had recently given birth participating in this study and selected through a simple random sampling technique. Data were collected using a face-to-face interview with pretested semi-structured questionnaires. The Epi-Data software (version 3.1) was used to record collected data and then exported to SPSS (version 23) for statistical analysis. Bi-variable and multivariable analyses were conducted and the odds ratio with 95% CI was used to identify factors associated with delays in reaching health facilities. The statistical significance was declared at p < 0.05. Results: The prevalence of delay in reaching health facilities among mothers who gave birth in south Gondar zone hospitals was 50.6%. Mothers who had no ANC visit [AOR = 3.16, 95% CI = 1.52, 6.56], unplanned pregnancy [AOR = 1.78, 95% CI = 1.16, 2.72], and a distance from home to health facility greater than five kilometers [AOR = 1.69, 95% CI = 1.08, 2.65] were positively associated with delays in reaching health facilities. Conclusions: The prevalence of delays in reaching health facilities was higher in the study area. Women's empowerment through health education about ANC follow-up, choice of family planning methods, and creating accessibility to health facilities are essential measures to minimize delays in reaching health facilities.